Fatu-Hiva back to nature - Heyerdahl, Thor; Zanesville Art Center Collection (Garden City, New York Doubleday Company, Inc., 1975)
The story of Heyerdahl and his wife's first Pacific adventure in 1936. Fatu-Hiva lay outside the shipping lanes; there were no white inhabitants and no contact with the outside world.
Farewell to civilization -- Back to nature -- White men, dark shadows -- Exodus -- Taboo -- Ocean escape -- On Hivaoa -- Island of ill omen -- In the cannibal valley -- Cave dwellers.
Includes bibliographical references and index.
Keywords: Heyerdahl, Thor; Fatuhiva Island (French Polynesia) -- Description and travel